Posters 2017
DOI: 10.1136/archdischild-2017-313273.252
|View full text |Cite
|
Sign up to set email alerts
|

P164 Faecal calprotectin levels in the babies with infantil colic

Abstract: IntroductionExcessive crying is a common semptom in the first three months of life. This situation named as infantile colic (first three months colic) is seen 10%–40% of the babies. Some theories were asserted in order to explain infantile colic, however they could not explain the aetiology in a certain way. In recent years, it is claimed that the changes in intestinal microbiota can result the colic. Measurement of faecal calprotectin showing the intestinal inflammation could be helpful for the diagnosis of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Some studies have shown the same result [15]. In the study of Karabayir et al on 70 infants, fecal Calprotectin was signi cantly higher in coliky infants compared to controls and similar to our study they showed that infant's birth weight had no effect on fecal calprotectin [22].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Some studies have shown the same result [15]. In the study of Karabayir et al on 70 infants, fecal Calprotectin was signi cantly higher in coliky infants compared to controls and similar to our study they showed that infant's birth weight had no effect on fecal calprotectin [22].…”
Section: Resultssupporting
confidence: 90%
“…In our study there was no signi cant difference between calprotectin levels regarding dietary patterns. This nding is consistent with some studies [13,17,22].However, the results of Asgarshirazi's study showed that breastfed infants had signi cantly higher levels of calprotectin in their feces (9). Drosko studied 15 infants with exclusively breastfeeding and 21 infants with a combination feeding.…”
Section: Resultssupporting
confidence: 86%